2017
DOI: 10.1017/ice.2017.180
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Improvement and Sustainability: Assessing a Breakthrough Collaborative in Western Switzerland

Abstract: objective. To assess hand hygiene improvement and sustainability associated with a Breakthrough Collaborative.design. Multicenter analysis of hand hygiene compliance through direct observation by trained observers.setting. A total of 5 publicly funded hospitals in 14 locations, with a total of 1,152 beds, in the County of Vaud, Switzerland.participants. Clinical staff.interventions. In total, 59,272 opportunities for hand hygiene were monitored for the duration of the study, for an average of 5,921 per audit (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…26,36,37 Our experience with this program reinforced the findings of other studies that a multimodal, team-driven, friendly competition and positive-reinforcement-focused approach is crucial for improving hand hygiene, particularly with respect to peer influence and role modeling. 11,12,28,29,38 It also reflects the assertion outlined in other studies that multimodal interventions are necessary for sustained improvement. 26,39,40 Easing concerns about the system's accuracy and increasing comfort were important considerations.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…26,36,37 Our experience with this program reinforced the findings of other studies that a multimodal, team-driven, friendly competition and positive-reinforcement-focused approach is crucial for improving hand hygiene, particularly with respect to peer influence and role modeling. 11,12,28,29,38 It also reflects the assertion outlined in other studies that multimodal interventions are necessary for sustained improvement. 26,39,40 Easing concerns about the system's accuracy and increasing comfort were important considerations.…”
Section: Discussionsupporting
confidence: 58%
“…26 Interventions that are associated with improved adherence include providing feedback, rewarding positive behavior, encouraging friendly competition, and conducting educational programs to raise awareness. [26][27][28][29][30] Our institution implemented an RFID-based AHHMS in selected units, coupled with interventions designed to increase hand hygiene adherence. We assessed hand hygiene adherence both electronically and by direct observation, and we studied the effect of AHHMS-measured adherence on HAI rates.…”
mentioning
confidence: 99%
“…The absence of leadership engagement in this study could also have been partially responsible for the modest improvement. Effective leadership involvement can improve hand hygiene compliance (25,26). Continuing efforts and further interventions are needed to address such issues.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of leadership has been linked with loss of sustainable change in hand hygiene compliance (34). Other studies have shown that inclusion of administrative leadership is linked with improvements in hand hygiene compliance rates and most importantly with enhanced sustainability of such improvements (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Infection Control and Hospital Epidemiology , Dr Staines et al 2 present the results of a well-organized, multifaceted, 18-month hand hygiene improvement collaborative project with a 12-month postimplementation assessment. A consortium of 5 Swiss hospitals participated, each setting up implementation teams that focused on systems optimization, education, data collection and feedback, leadership, and “sustainability engineering,” a set of interventions aimed at maintaining the effect of their interventions after the project was completed.…”
mentioning
confidence: 99%